2017
DOI: 10.1111/pce.12943
|View full text |Cite
|
Sign up to set email alerts
|

Algal light sensing and photoacclimation in aquatic environments

Abstract: Anoxygenic photosynthetic prokaryotes arose in ancient oceans ~3.5 billion years ago. Evolution of oxygenic photosynthesis by cyanobacteria followed soon after, enabling eukaryogenesis and the evolution of complex life. The Archaeplastida lineage dates back ~1.5 billion years to the domestication of a cyanobacterium. Eukaryotic algae have subsequently radiated throughout oceanic/fresh-water/terrestrial environments, adopting distinctive morphological and developmental strategies for adaptation to diverse light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 145 publications
0
41
0
4
Order By: Relevance
“…Both SSA01 and SSB01 possess putative rhodopsins, phytochrome-like and cryptochrome proteins, although other or unusual photoreceptors might also be responsible for sensing the light signal (Duanmu et al 2017). There are a higher number of putative cryptochrome encoding genes in SSA01 and SSB01 (20 in A4: Xiang, T. unpublished data;18 in B1: Xiang, et al 2015) than genes encoding other identified photoreceptors, which could reflect an increased number of algal responses to blue light.…”
Section: Phototaxis Under Red Lightmentioning
confidence: 99%
See 1 more Smart Citation
“…Both SSA01 and SSB01 possess putative rhodopsins, phytochrome-like and cryptochrome proteins, although other or unusual photoreceptors might also be responsible for sensing the light signal (Duanmu et al 2017). There are a higher number of putative cryptochrome encoding genes in SSA01 and SSB01 (20 in A4: Xiang, T. unpublished data;18 in B1: Xiang, et al 2015) than genes encoding other identified photoreceptors, which could reflect an increased number of algal responses to blue light.…”
Section: Phototaxis Under Red Lightmentioning
confidence: 99%
“…Symbiotic cnidarians have adapted to a wide range of photic environments, with exposure to different light regimes that vary over seasons and with depth in the water column (Gattuso et al 1995). Furthermore, the holobiont has various photoreceptors (chromophore-associated proteins) including the blue-green light-absorbing rhodopsins, potentially the red/far red light-absorbing photoreversible phytochromes and the blue light-absorbing cryptochromes and phototropins (Duanmu et al 2017). These photoreceptors detect light signals and elicit downstream responses associated with circadian rhythms, photomorphogenesis and other physiological responses (Somers et al 1998;Delvin and Kay 2000;Christie et al 2015;Kong and Okajima 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Among the genes associated with light sensing in Chlamydomonas, cryptochromes and phototropin appear to be obvious candidates to play roles in blue-light-dependent regulatory mechanisms (Huang et al, 2002;Zorin et al, 2009;Ahmad, 2016;Petroutsos et al, 2016;Duanmu et al, 2017Zou et al, 2017). Among the five genes encoding cryptochrome (CRY) photoreceptors (for a recent review on algal CRYs, see Duanmu et al, 2017;Kottke et al, 2017), expression levels for the gene encoding plant CRY (pCRY) are highest, peak in the dark, and are rapidly repressed upon the onset of light.…”
Section: Hmox1 Is Dispensable For Light-dependent Transcript Accumulamentioning
confidence: 99%
“…Among the five genes encoding cryptochrome (CRY) photoreceptors (for a recent review on algal CRYs, see Duanmu et al, 2017;Kottke et al, 2017), expression levels for the gene encoding plant CRY (pCRY) are highest, peak in the dark, and are rapidly repressed upon the onset of light. This is similar to diurnal conditions where transcripts of pCRY were found to be highest during the night and rapidly declined during the day (Zones et al, 2015).…”
Section: Hmox1 Is Dispensable For Light-dependent Transcript Accumulamentioning
confidence: 99%
See 1 more Smart Citation